2022
DOI: 10.1007/s10844-022-00736-2
|View full text |Cite|
|
Sign up to set email alerts
|

Deep learning based sentiment analysis of public perception of working from home through tweets

Abstract: Nowadays, we are witnessing a paradigm shift from the conventional approach of working from office spaces to the emerging culture of working virtually from home. Even during the COVID-19 pandemic, many organisations were forced to allow employees to work from their homes, which led to worldwide discussions of this trend on Twitter. The analysis of this data has immense potential to change the way we work but extracting useful information from this valuable data is a challenge. Hence in this study, the microblo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 47 publications
(55 reference statements)
0
9
0
Order By: Relevance
“…In addition, eight emotions were evaluated, from which it is concluded that in most tweets, a connotation of confidence, anticipation, and joy prevails. Vohra and Garg (2023) argued that there is evidence of a growing preference for working from home, according to the data obtained from Twitter; to the extent that 54.41% of the tweets show a positive and satisfactory opinion, compared to 24.50% where dissatisfac-tion is observed. These results contrast with Gutierrez-Lythgoe ( 2023), who performed a sentiment analysis using a deep learning model for natural language processing where he shows that 43.5% of the tweets analyzed present a negative connotation, concerning 35.5% where neutrality is observed and 21.1% with a positive connotation.…”
Section: Social Network and Teleworkingmentioning
confidence: 99%
“…In addition, eight emotions were evaluated, from which it is concluded that in most tweets, a connotation of confidence, anticipation, and joy prevails. Vohra and Garg (2023) argued that there is evidence of a growing preference for working from home, according to the data obtained from Twitter; to the extent that 54.41% of the tweets show a positive and satisfactory opinion, compared to 24.50% where dissatisfac-tion is observed. These results contrast with Gutierrez-Lythgoe ( 2023), who performed a sentiment analysis using a deep learning model for natural language processing where he shows that 43.5% of the tweets analyzed present a negative connotation, concerning 35.5% where neutrality is observed and 21.1% with a positive connotation.…”
Section: Social Network and Teleworkingmentioning
confidence: 99%
“…The proposed deep learning model includes convolution, max pooling, dropout, and dense layers with ReLU and sigmoid activations, achieving a remarkable accuracy of 0.925969 on the dataset. The results compare positively against other classifiers, and tweets are found to have informational (54.41%), negative (24.50%), and neutral (21.09%) sentiments related to working from home [21].…”
Section: Related Workmentioning
confidence: 76%
“…Furthermore, the dataset is subjected to data pre-processing, which includes data cleaning, case folding, tokenization, word normalization, and data variation. Data cleaning is done to clean unnecessary characters, hyperlinks, Unicode, and so on [9]. Case folding is done to change capital letters to lowercase letters in a sentence as a whole [10].…”
Section: Dataset Preparationmentioning
confidence: 99%